Kota Tua Jakarta Revitalization: An Effort to Embody Human Rights City in Railways Track's Vicinity During the Covid-19 Pandemic - Wibowo, Aji; Sujatmoko, Andrey; Permanasari, Arlina; Zuhra, Amalia; Justinar, Jun; I. Notoprayitno, Maya (KnE Social Sciences, 2022)
Kota Tua area in West Jakarta, especially around the railroad tracks, is still inhabited by the poor of Jakarta. The cultural heritage-based revitalization of the Kota Tua Jakarta Area essentially requires the residents who live in the vicinity of the railway line area to be relocated to a safer place which will certainly have an impact on the surrounding residents. This study discusses whether Governor’s Regulation No. 36/2014 is in line with the Gwangju Declaration in realizing the revitalization of the Kota Tua Jakarta area. Also, how is the fulfillment of the right to housing around the railroad tracks related to preventthe spread of COVID-19 in the Kota Tua Jakarta area? Hence, this can be answered through the urgency and priority scale of human rights implementation in the Kota Tua Jakarta Area, specifically in the vicinity of the railroads track, including during the outbreak of Covid-19. This research is a normative juridical with qualitative analysis of the legal norms of national legislation related to the implementation of human rights. The analysis is qualitative, and based on a systematic literature review over scientific journal database. The results of this research show that the protection of human rights for the residents living in the vicinity of the railway line is still not fully implemented. For this reason, it is necessary to implement regulations to ensure respect and guaranteed human rights to the residents, especially the right to health, the right to education, the right to food, including the right to a healthy environment. Keywords: Kota Tua Jakarta, revitalization, human rights city